Comparative morph-anatomical studies on selected Sudanese medicinal plants: part iv. abutilon figarianum and abutilon pannosum leaves - ELtahir, Manasik; EL-Kamali, Hatil; Salih, Ahlam (International Journal of Scientific World, 2017)
In this study, macro and micro morphology of the leaves of Abutilon figarianum and Abutilon pannosum(Malvaceae) were compared to assist as a relevant source of information and contribute towards the standards to dispose the quality and identity of these plants to avoid adulterations. Laminar size, shape, marginal type, leaf length, width, petiole length, leaf base angle and leaf apex angle were observed and measured. The relationships were illustrated by differences of radar shape. Transverse sections of the leaves were done using wax method. Three regions from each leaf were sectioned apex, middle and base. The epidermises formed of one layer of small polygonal cells covered by mucilage, large numbers of epidermal hairs appeared. The two leaves are dorsiventral. The vascular bundles arch shaped surrounded by collenchymas and ground parenchyma. Xylem consists of radial rows of cells. The phloem is found beneath. The structures at the apex, middle and bases of the leaves are similar, trichomes are denser in the middle region followed by the upper and lastly the lower region. Calcium oxalate druses are appeared in some parenchyma cells of the mid rib region, and these are of large numbers in the basal region.